Posthumanism: A Political Perspective: Review of Cary Wolfe, What is Posthumanism? - Geroux, Robert (Humanimalia, 2013)
Cary Wolfe. What is Posthumanism? (Posthumanities.) Minneapolis: University of Minnesota Press, 2009. 400 pp. 75.00 hb; 24.95 pb; 14.97 kindle.